Brexit, UK Manufacturing and Industrial Strategy - Bailey, David; Rajic, Ivan (Border Crossing, 2025)
This paper offers an overview of the impacts of Brexit on UK manufacturing. In particular it looks at impacts via non-tariff barriers in terms of goods exports, imports, and UK manufacturing’s position in European value chains. It then looks at regulatory divergence and its implications for UK manufacturing. The need for an industrial strategy is examined. Overall, we find that post-Brexit the UK economy is less open to trade and investment, reducing UK manufacturing competitiveness and its ability to compete in both EU and global markets. The government’s new industrial strategy needs to address major issues facing the sector such as skills, investment, scaling-up new clean technologies, as well as ongoing post-Brexit uncertainties.